Surgical strategies of complicated pheochromocytomas/paragangliomas and literature review - Wang, Xu; Zhao, Yang; Liao, Zhangcheng; Zhang, Yushi (Frontiers in Endocrinology, 2023)
Surgical strategies of complicated pheochromocytomas/paragangliomasPheochromocytomas (PCC)/paragangliomas (PGL) are catecholamine (CA) -secreting neuroendocrine tumors, which are known as PPGL due to their histological and pathophysiological similarities. In addition to the typical triad of paroxysmal headache, palpitation, and sweating, PPGL may also be accompanied by symptoms and signs involving multiple organ systems such as cardiovascular system, digestive system, endocrine system, and nervous system. Currently, surgical resection is the first choice for PPGL. Safe and effective surgical management of complicated PPGL is the goal in clinical work. In this paper, we discuss this hot issue based on the complicated PPGL cases, aiming to share our experience of the surgical management strategy of PPGL.